2002
DOI: 10.1086/338235
|View full text |Cite
|
Sign up to set email alerts
|

Imported Falciparum Malaria in Europe: Sentinel Surveillance Data from the European Network on Surveillance of Imported Infectious Diseases

Abstract: Malaria continues to have a high morbidity rate associated among European travelers. Thorough recording of epidemiological and clinical aspects of imported malaria has been helpful in the detection of new outbreaks and areas of developing drug resistance. Sentinel surveillance of data collected prospectively since 1999 has begun within TropNetEurop, a European network focusing on imported infectious diseases. TropNetEurop appears to cover approximately 10% of all patients with malaria seen in Europe. Reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
102
1
16

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(129 citation statements)
references
References 8 publications
10
102
1
16
Order By: Relevance
“…The univariate analysis indicates that malaria acquired in Africa has a higher CFR than malaria acquired elsewhere ( 10 , 13 ). Lewis et al have shown that severe malaria was observed more commonly in patients returning from countries in central, southern, and eastern Africa compared to those returning from countries in western Africa ( 15 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The univariate analysis indicates that malaria acquired in Africa has a higher CFR than malaria acquired elsewhere ( 10 , 13 ). Lewis et al have shown that severe malaria was observed more commonly in patients returning from countries in central, southern, and eastern Africa compared to those returning from countries in western Africa ( 15 ).…”
Section: Discussionmentioning
confidence: 96%
“…Because fatal malaria is rare in nonendemic countries, various studies on imported malaria have not had the statistical power to investigate the case-fatality rate under inclusion of relevant confounders ( 8 , 9 ). Multinational networks able to overcome the problem of small sample size collect their data from specialized centers, causing a number of selection biases that may have particular impact on the CFR ( 8 , 10 ). …”
mentioning
confidence: 99%
“…This improvement in sensitivity affected mainly falciparum malaria. P. falciparum is the most frequently detected agent of imported malaria, especially in the European Union where the closest endemic zone is sub-Saharan Africa (Jelinek et al, 2002). Moreover, even chemoprophy-S ince the first description, in 1990, of the diagnosis of Plasmodium falciparum infection by means of polymerase-chain-reaction (PCR) (Jaureguiberry et al, 1990), the role of this kind of molecular method in the laboratory diagnosis of imported malaria is still a topical question.…”
mentioning
confidence: 99%
“…It is still under debate whether malaria parasites have evolved specific immune evasion mechanisms that interfere with memory formation. There are several reports of previously immune immigrants losing their immunity to malaria after a certain time of residence in a nonendemic area; however, systematic surveys imply that previously immune adults residing in nonendemic areas maintain a lower risk of severe and fatal disease [7][8][9].It was shown by using irradiated or genetically attenuated sporozoites that sterile protection can be achieved by the induction of a T-cell response directed against infected hepatocytes [10][11][12][13]. In addition, a liver-stage-specific vaccine has the advantage that it could prevent the pathology associated with the blood-stage of the disease.…”
mentioning
confidence: 99%
“…It is still under debate whether malaria parasites have evolved specific immune evasion mechanisms that interfere with memory formation. There are several reports of previously immune immigrants losing their immunity to malaria after a certain time of residence in a nonendemic area; however, systematic surveys imply that previously immune adults residing in nonendemic areas maintain a lower risk of severe and fatal disease [7][8][9].…”
mentioning
confidence: 99%